Analisis Kemampuan Berpikir Kreatif Matematis Ditinjau dari Gaya Kognitif dan Gender - Nabila Ramadhani Maryanto; Rizki Dwi Siswanto (Universitas Muria Kudus, 2021)
This study aims to describe and analyze students’ mathematical creative thinking ability in terms of cognitive style and gender. The research method used is descriptive qualitative. The sampling technique was purposive sampling with the subject of this study were 4 students, consisting of 1 male student with a reflective cognitive style, 1 male student with an Impulsive cognitive style, 1 female student with a reflective cognitive style, and 1 female students with Impulsive cognitive style. The instruments in this study were the Matching Familiar Figure Test (MFFT) and mathematical creative thinking skills. Data analysis in this study is by data reduction and categorization, data presentation, and drawing conclusions. The triangulation technique was used to validate the data by comparing the test results of the subject’s mathematical creative thinking ability with the interview. The conclusion of this study is that male gender subjects (namely S1 and S3), both reflective and impulsive cognitive styles are more able to think more flexibly by providing some prism netting images or some correct answers when solving math problems than female gender subjects ( namely S2 and S4) with reflective and impulsive cognitive style. Meanwhile, female gender subjects with impulsive cognitive style (S4) can provide detailed answers and have better accuracy than male gender subjects (S1 and S3)